Sudden death of a crossbred calf associated with a myocardial adenomatoid tumour. Issue 6 (June 2018) - Slocombe, RF
Abstract : The only lesion found in a crossbred calf that died suddenly was a rare tumour in the myocardium of the left ventricle. The mass appeared similar to tumours discovered incidentally in the hearts of abattoir specimens in Italy, described as adenomatoid tumours. These are bimorphic tumours presumed to have a mesothelial origin. Although in a published study from Italy these tumours were considered incidental and clinically unimportant, I suggest that in this case the mass may have interfered with cardiac conduction, causing sudden death of the calf.